The Community Nursing Care In RT 01 And RW 02 Hamlet Mountain Three Village Cintaratu Pangandaran Parigi District - Purnama, Dadang; Setiawan, Setiawan; Witdiawati, Witdiawati; Sunarya, Uu (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Community health nursing is a very strategic field and plays an active role in improving the health status of the community. According to the World Health Organization (WHO) in 2009, 60-80% of health services in the world are provided by nurses, while in Africa almost 85% of health services are provided by nurses. Nursing care that has been carried out in the Gunungtiga Hamlet community RT 01 and 02 RW 06 Cintaratu Village can be concluded that there are several nursing problems that arise in the Gunungtiga community with the priority problem being Ineffective Health Care. As well as the implementation activities that have been carried out, namely exercise and health education related to the effectiveness of aerobic exercise and tomato juice in reducing blood glucose levels, also went smoothly and received good evaluations. , community nursing is a very strategic field and plays an active role in improving the health status of the community. So we as medical personnel should apply the concepts and theories of community nursing to the community directly that have been studied previously.